A new species of African Forest Robin from Gabon (Passeriformes: Muscicapidae: Stiphrornis) - Schmidt, Brian K.; Foster, Jeffrey T.; Angehr, George R.; Durrant, Kate L.; Fleischer, Robert C. (Zootaxa, 2008)
We describe a new species of forest robin from the Gamba Complex in southwest Gabon. This common bird, Stiphrornis pyrrholaemus sp. nov., inhabits primary lowland forest and forages on or near the ground like the other members of the genus Stiphrornis of central and western Africa. Unique phenotypic features of the new species include the male’s bright orange chin, throat, and breast, creamy yellow belly, olive green back and rump, and gray flanks. Mitochondrial sequence divergence corroborates our assessment based on its distinct physical characteristics that this is a new species, and suggest that Stiphrornis erythrothorax is likely the most closely related congener.